Tax Policy and Inclusive Growth. (IMF Working Papers; Working Paper ;, 2020)
This paper discusses the theory and practice of tax design to achieve an efficient and equitable outcome, id est in support of inclusive growth. It starts with a discussion of the key principles from tax theory to guide practical tax design. Then, it elaborates on more granular tax policy, discussing key choices in the structure of the personal income tax on labor and capital income, taxes on wealth, the corporate income tax, and consumption taxes. The paper concludes by highlighting the political economy considerations of the issues with concrete recommedtions as to how to implement tax reform.